Stigmatization of People with Disability in Nepal - Subedi, Tek Nath (SMC Journal of Sociology, 2025)
Individuals with disabilities constitute a surprisingly small segment of Nepal's total population. Notwithstanding the prolonged Maoist-led insurgency in Nepal leading to a heightened incidence of disabilities, social stigma attached to disability and under-reporting of disability cases remain widespread. The opportunities for education and employment for individuals with disabilities are restricted due to societal perceptions, leading many to choose not to disclose their disabilities in order to avoid stigma. Society often views individuals with disabilities as burdens and lacking the capacity for independence, with discrimination beginning at birth. Additionally, families strive to conceal their disabled members to protect their social reputation. This paper tries to examine the societal stigma associated with individuals having physical, visual and hearing disabilities in Kathmandu. Participants expressed the emotional exhaustion of consistently having to showcase their capabilities, facing bias, and experiencing social exclusion driven by cultural superstitions such as stigma. Many people with disabilities exhibit a variety of skills; however, societal perceptions frequently overlook these abilities and reinforce persistent stigmas. Blind people encounter substantial obstacles, including societal perceptions of dependency and inadequacy. Misconceptions impede employment opportunities and social relationships, especially for women who face greater scrutiny. The outcome is emotional stress and social isolation. Addressing these challenges requires a change in societal perspectives, emphasizing abilities rather than disabilities, ensuring open space, and fostering inclusion to counteract pervasive biases.